PENGARUH ANALISIS JABATAN, KUALITAS SUMBER DAYA MANUSIA (SDM), DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN POHUWATO - Ibrahim, Meimoon; Hasanuddin, Hasanuddin; R. Karundeng, Deby; Usman Rasid, Ayub; Hasan, Fony (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to analyze the influence of job analysis, human resource (HR) quality, work discipline, and work environment on employee performance at the Regional Disaster Management Agency (BPBD) of Pohuwato Regency. This research employs a quantitative approach using a survey method by distributing questionnaires to 33 BPBD employees in Pohuwato Regency. Data analysis techniques utilize multiple linear regression with the assistance of SPSS version 25 software. The results indicate that job analysis, HR quality, and work environment variables have a positive and significant effect on employee performance. This suggests that better job analysis, higher HR quality, and a more conducive work environment lead to improved employee performance. Conversely, the work discipline variable has a negative and significant effect on employee performance, indicating that excessively strict or inflexible work discipline implementation can negatively impact employee performance. Simultaneously, the four independent variables have a positive and significant influence on employee performance at BPBD Pohuwato Regency. Based on these findings, improving HR quality and the work environment should be the primary focus in efforts to enhance employee performance at BPBD Pohuwato Regency. Additionally, further evaluation of work discipline policies is needed to ensure they are more adaptive to the working conditions of BPBD employees